Encapsulation of Human-Bone-Marrow-Derived Mesenchymal Stem Cells in Small Alginate Beads Using One-Step Emulsification by Internal Gelation: In Vitro, and In Vivo Evaluation in Degenerate Intervertebral Disc Model - Sarit S. Sivan; Iris Bonstein; Yariv N. Marmor; Gadi Pelled; Zulma Gazit; Michal Amit (MDPI AG, 2022)
Cell microencapsulation in gel beads contributes to many biomedical processes and pharmaceutical applications. Small beads (<300 µm) offer distinct advantages, mainly due to improved mass transfer and mechanical strength. Here, we describe, for the first time, the encapsulation of human-bone-marrow-derived mesenchymal stem cells (hBM-MSCs) in small-sized microspheres, using one-step emulsification by internal gelation. Small (127-257 µm) high-mannuronic-alginate microspheres were prepared at high agitation rates (800-1000 rpm), enabling control over the bead size and shape. The average viability of encapsulated hBM-MSCs after 2 weeks was 81 ± 4.3% for the higher agitation rates. hBM-MSC-loaded microspheres seeded within a glycosaminoglycan (GAG) analogue, which was previously proposed as a mechanically equivalent implant for degenerate discs, kept their viability, sphericity, and integrity for at least 6 weeks. A preliminary in vivo study of hBM-MSC-loaded microspheres implanted (via a GAG-analogue hydrogel) in a rat injured intervertebral disc model demonstrated long-lasting viability and biocompatibility for at least 8 weeks post-implantation. The proposed method offers an effective and reproducible way to maintain long-lasting viability in vitro and in vivo. This approach not only utilizes the benefits of a simple, mild, and scalable method, but also allows for the easy control of the bead size and shape by the agitation rate, which, overall, makes it a very attractive platform for regenerative-medicine applications.